2020
DOI: 10.1155/2020/3497810
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Three-DNA Methylation Signature as a Novel Prognostic Biomarker in Patients with Colorectal Cancer

Abstract: Aims. The prognosis of colorectal cancer (CRC) remains poor. This study aimed to develop and validate DNA methylation-based signature model to predict overall survival of CRC patients. Methods. The methylation array data of CRC patients were retrieved from The Cancer Genome Atlas (TCGA) database. These patients were divided into training and validation datasets. A risk score model was established based on Kaplan-Meier and multivariate Cox regression analysis of training cohort and tested in validation cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…7-12 14 28 30 The equation to calculate prognostic score, the distribution of each prognostic score in our validation cohort, and the performance of these models reported by original development studies are shown in Supplementary Table 6. Five prognostic models from four studies 8-10 14 were independently associated with OS (Supplementary Table 7). The relationships between the prognostic scores and survival were largely linear (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7-12 14 28 30 The equation to calculate prognostic score, the distribution of each prognostic score in our validation cohort, and the performance of these models reported by original development studies are shown in Supplementary Table 6. Five prognostic models from four studies 8-10 14 were independently associated with OS (Supplementary Table 7). The relationships between the prognostic scores and survival were largely linear (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study handled missing values properly by multiple imputations, 9 while the remaining studies either excluded patients with missing values or did not report this information. Four out of nine studies (44%) did not take measures to account for model overfitting, 7 8 10 14 and three of the nine studies selected CpGs simply based on the p -values in univariable and multivariable analyses without considering established clinical knowledge. 8 14 28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This classifier included probes in BRD4, FBXL18, KCNQ1 and MET, among others, and the DNA methylation score of this panel was positively correlated with patient survival [61]. (3) Gong et al mined TCGA CRC DNA methylation data to compile a three-gene (NR1H2, SCRIB and UACA) DNA methylation signature that correlated with patient OS irrespective of patient age and gender [62]. (4) Xie et al [63] used tumor-derived cfDNA from blood plasma to evaluate the performance of a 14-gene panel (ARHGEF4, AV3, BMP3, CHST2, DOCK10, IKZF1, LRRC4, NDRG4, OPLAH, PPP2R5C, PDGFD, QKI, SFMBT2 and ZNF625).…”
Section: Dna Methylation Alterationsmentioning
confidence: 99%